Realidade aumentada no ensino de língua inglesa: contribuições da formação de formadores - Oliveira, Jayne dos Santos (2024)
This research aims to understand the contributions of the training of trainers in the construction of an English language teacher training course for the use of augmented reality, during the realization of an international cooperation project financed by FAPITEC and developed, in the year 2021, between the Federal University of Sergipe, the Sergipe State Department of Education and Culture and the University of Miami. The theoretical framework is based on authors who discuss the use of digital information and communication technologies in education, the insertion and practice of augmented, virtual and mixed reality in English language teaching, the training of trainers to build skills in the association of immersive technologies and teaching and teacher training. This is a qualitative study, characterized as participatory action research, and is part of the Technologies, Languages and Education research line. Data were collected through recordings of meetings held during the training of trainers on an online platform. The data analysis is based on the combined model of Freeman's Teaching Research (1998) and the coding processes of Auerbach and Silverstein (2003) proposed by Santos (2020) and Santos (2021). Some of the desired outcomes include non-hierarchical relationships and conscious constructions of teacher training in technologies, the possibilities of inserting immersive technologies in English language teaching in the context of public basic education in Sergipe, and perceptions of possibilities between previous training directed at trainers and the offers of teacher training.